PENGINTEGRASIAN HIGHER ORDER THINKING SKILLS KE DALAM PEMBELAJARAN TEMATIK TERPADU DI MIN 2 JEMBER - Alfiah, Alfiah Alfiah (IJIT: Indonesian Journal of Islamic Teaching, 2022)
ABSTRAK Facing era 4.0 is required by a quality Indonesian generation to be able to compete, side by side and even compete in the era of globalization, which is full of various problems and challenges that are increasingly complicated and complex. Therefore, learning is needed in accordance with the needs of the times, namely integrating 21st century learning in the process of teaching and learning in the classroom. Research Focus is: 1) How is the integration of HOTS into integrated thematic learning planning in MIN 2 Jember? 2) How is the integration of HOTS into the implementation of integrated thematic learning in MIN 2 Jember? 3) How is hots integrated into integrated thematic learning evaluation in MIN 2 Jember?. This research uses a descriptive qualitative approach. The research subjects are the Head of Madrasah, Teachers and students of MIN 2 Jember. Data collection techniques use observation, interviews and documentation. Data analysis techniques using Miles and Hubberman model analysis The results of this study can be concluded that: 1) HOTS integration activities into integrated thematic learning planning at MIN 2 Jember are carried out through RPP planning to achieve HOTS learning and assessment goals. By using RPP or learning planning aims to be an archetype in arranging student tasks, so that in the learning process and final assessment are related to each other. 2) Integration of HOTS into the implementation of integrated thematic learning at MIN 2 Jember. Covering is the preliminary, core, and closing activities.. 3) The integration of HOTS into evaluation in integrated thematic learning in MIN 2 Jember consists of self-evaluation and group. ABSTRAK Era 4.0 menuntut generasi Indonesia harus mampu bersaing, bersanding bahkan bertanding dalam era globalisasi. Oleh karena itu dibutuhkan pembelajaran yang sesuai dengan kebutuhan zaman yaitu mengintegrasikan pembelajaran abad 21 dalam proses belajar mengajar di kelas. Fokus Penelitian ini yaitu: 1) Bagaimana pengintegrasian HOTS ke dalam perencanaan pembelajaran tematik terpadu di MIN 2 Jember?, 2) Bagaimana pengintegrasian HOTS ke dalam pelaksanaan pembelajaran tematik terpadu di MIN 2 Jember? 3) Bagaimana pengintegrasian HOTS ke dalam evaluasi pembelajaran tematik terpadu di MIN 2 Jember? Penelitian ini menggunakan pendekatan kualitatif deskriptif. Subjek penelitian yaitu Kepala Madrasah, Guru dan siswa MIN 2 Jember. Tekhnik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Tekhnik analisis data dengan menggunakan analisis model Miles dan Hubberman. Hasil penelitian dapat disimpulkan bahwa: 1) Kegiatan pengintegrasian HOTS ke dalam perencanaan pembelajaran tematik terpadu di MIN 2 Jember dilakukan melalui perencanaan RPP untuk mencapai tujuan pembelajaran dan penilaian HOTS. 2) Pengintegrasian HOTS ke dalam pelaksanaan pembelajaran tematik terpadu di MIN 2 Jember meliputi aktifitas pendahuluan, inti, dan penutup. 3) Pengintegrasian HOTS ke evaluasi dalam pembelajaran tematik terpadu di MIN 2 Jember terdiri dari evaluasi mandiri dan kelompok.